Generalized Reddish Skin Nodules - Laniyati Hamijoyo; Dinar F Yaddin; Indra Wijaya; Panji Irani Fianza; Hermin Aminah Usman; Bethy S Hernowo; Harjuli Yoy Ceana; Miranti Pangastuti; Yovita Hartantri (Interna Publishing, 2023)
Diagnosis of nodular red lesions is challenging. The differential diagnosis includes dermal nevus, angioma, pyogenic granuloma, amelanotic melanoma, eccrine poroma, Kaposi's sarcoma, skin malignancy or metastasis. Erythema nodosum is one of the common consideration of the red skin nodules, however fully work up should be done to find the right diagnosis. A 60 years old female admitted to our hospital due to pain dark reddish skin nodules since one month. She had continuously high grade fever of 39 Celsius accompanied by arthralgia and fatigue since two months prior to admission and she lost 6 kg of weight in 2 months. On admission, physical examination revealed slight fever, pale conjunctiva, mild hepatosplenomegaly, tender dark red nodules 0.3 to 2 cm, firm edge, at her cheek, abdominal area and both lower extremities. No lymph nodes enlargement was noticed. Her laboratory test showed haemoglobin 9,1 g/dl, WBC 3,040/mL, PLT 149,000/mL, SGOT 48 U/L, SGPT 43 U/L, urea 12.5 mg/dL, creatinine 0.67 mg/dL. She was found to be non-reactive for HBsAg, HCV, and HIV antigens. Urine routine and microscopic examination was unremarkable. Her histopathology of left foot nodule biopsy revealed cutaneous lymphoma. The immunohistochemical (IHC) stain of CD45, CD20, and CD10 were positive, Ki67 were also positive  with >70% tumor cells, while CD3,CD56, CD30, and Granzyme were negative. Her final diagnosed was Cutaneous Diffuse large B cell lymphoma. Primary cutaneous lymphomas of B-cells occur less frequently than primary cutaneous T-cells lymphomas. Primary extra-nodal diffuse large B-Cell lymphoma (DLBCL) can be seen in up to 40% of cases. However skin involvement is less common and in a large cohort of DLBCL cases, skin involvement at presentation was seen only in 3.3% of cases.It characterized by few lesions, in general showing nodules or infiltrations of relatively fast growth and have no itching. The diagnosis is made by the immunohistochemical findings, clinicopathological correlation, and molecular pathology.  The lymphomas have different clinical behaviours despite being identical in morphological appearance. The primary lymphomas presents with local recurrence in up to 68% of the cases and with rare extra-cutaneous dissemination, with an average rate of 5-year survival varying from 89 to 96%. Cutaneous lymphoma should be always become one of considered diagnosed of skin red nodules even it is rare.